Outcomes of MIS-C patients treated with anakinra: a retrospective multicenter national study - Licciardi, Francesco; Covizzi, Carlotta; Dellepiane, Marta; Olivini, Nicole; Mastrolia, Maria Vincenza; Lo Vecchio, Andrea; Monno, Viviana; Tardi, Maria; Mauro, Angela; Alessio, Maria; Filocamo, Giovanni; Cattalini, Marco; et al. (Frontiers in Pediatrics, 2023)
Background: The treatment of Multisystem Inflammatory Syndrome in children unresponsive to first-line therapies (IVIG and/or steroids) is challenging. The effectiveness of IL-1 receptor antagonist, anakinra, is debated. Patients and Methods: We conducted an anonymous retrospective multicenter study on MIS-C patients treated with anakinra in Italy from January 2020 to February 2021. Our study outcomes included the percentage of patients who required further therapeutic step-up, the percentage of patients who experienced fever resolution within 24 hours and a reduction of CRP by half within 48 hours, and the percentage of patients who developed Coronary Artery Anomalies (CAA) during follow-up. Results: 35 cases of MIS-C were treated in 10 hospitals. Of these, 13 patients started anakinra while in the ICU, and 22 patients started anakinra in other wards. 25 patients (71,4%) were treated with corticosteroids at a starting dose 2-30 mg/Kg/day plus IVIG (2g/Kg), 10 patients (28,6%) received only corticosteroids without IVIG. Anakinra was administered intravenously to all patients in Group A (mean dose 8 mg/Kg/day), and subcutaneously in Group B (mean dose 4 mg/Kg/day). Only two patients required further treatment step-up and no patients developed CAA after receiving anakinra. The most commonly observed side effect was an increase in ALT, occurring in 17.1% of patients. Conclusions: In this retrospective cohort of severe MIS-C patients treated with anakinra we report favorable clinical outcomes with a low incidence of side effects. The simultaneous use of steroidsIVIG in these patients hinders definitive conclusions regarding the need of IL-1 inhibition in MIS-C treatment.